Host species and site of collection shape the microbiota of Rift Valley fever vectors in Kenya. - David P Tchouassi; Ephantus J Muturi; Samwel O Arum; Chang-Hyun Kim; Christopher J Fields; Baldwyn Torto (Public Library of Science (PLoS), 2019)
The composition and structure of microbial communities associated with mosquitoes remain poorly understood despite their important role in host biology and potential to be harnessed as novel strategies for mosquito-borne disease control. We employed MiSeq sequencing of the 16S rRNA gene amplicons to characterize the bacterial flora of field-collected populations of Aedes mcintoshi and Aedes ochraceus, the primary vectors of Rift Valley fever (RVF) virus in Kenya. Proteobacteria (53.5%), Firmicutes (22.0%) and Actinobacteria (10.0%) were the most abundant bacterial phyla accounting for 85.5% of the total sequences. Non-metric multi-dimensional scaling plots based on Bray-Curtis dissimilarities revealed a clear grouping of the samples by mosquito species, indicating that the two mosquito species harbored distinct microbial communities. Microbial diversity, richness and composition was strongly influenced by the site of mosquito collection and overall, Ae. ochraceus had significantly higher microbial diversity and richness than Ae. mcintoshi. Our findings suggest that host species and site of collection are important determinants of bacterial community composition and diversity in RVF virus vectors and these differences likely contribute to the spatio-temporal transmission dynamics of RVF virus.